CONTEXTUAL TEACHING LEARNING (CTL) APPROACH IN SPEAKING MATERIALS FOR STUDENTS’ 21ST CENTURY SKILL: DOES IT HAVE ANY EFFECT? - Muliani Muliani; Dedi Sumarsono (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2019)
In this era, having only speaking competence is not adequate for the students.  They also need to possess some other skills like critical thinking which is also known as the 21st century skill. The 21st century learners must possess both self-direction and an ability to collaborate with individuals, groups, and machines. To support this, new speaking materials based on the context of the real world need to be used in teaching the students to ensure the EFL thinking critically is urgently needed. This paper is aimed at knowing the effect English speaking material which is based on contextual teaching learning towards EFL critical thinking in speaking. To achieve this purpose, the students were taught using speaking material which is based on contextual teaching-learning before the speaking test was taken at the end. To analyze the data t-test was applied. The data analysis showed that CTL had a significant effect on students’ critical thinking after being treated.